Analyze Financial Performance and Predict Bankruptcy Using the Du Pont and Altman Z-Score on PT Gojek Tokopedia Tbk Period 2020 - 2023 - Hidayatullah, Fajar; Nasution, Yenni Samri Juliati; Syafina, Laylan (Universitas Hamzanwadi, 2024)
This research aims to analyze the company's financial performance whether it is good or not and predict bankruptcy whether this company has the potential to go bankrupt or not, in addition to the researcher hopes that this research can be considered for readers or investors to invest in PT Gojek Tokopedia Tbk. This study uses a quantitative descriptive approach with secondary data and uses the Dupont and almant z-score methods. The results of this study show that the company's financial performance during the period 2020 – 2023 has not been good, which can be seen from the results of the Du Pont analysis which is still said to be far below the existing standard because the value of the average ROI during the period 2020 – 2023 is -111% with the industry standard > 20% and the average ROE value during the period 2020 – 2023 is -167% with the industry standard > 40%. And for the results of the bankruptcy analysis of the number of times the company has entered the bankruptcy danger zone, which can be seen from the results of the study using the Almant Z – Score method where in 2020 and 2023 the calculation values are -4.66 and -19.29 which is too far from the threshold of the set health standard of >2.6.